The hanging party - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Texas Lightning novel., 2024)
"His name is Jon Gage. But most folks know him as 'Texas Lightning,' the fastest draw in the West. The deadliest, too. Rumor has it he's killed more than thirty men in half as many years, a body count he won't deny. His reputation as a gunslinger, widowmaker, and all-around hellraiser inspires awe, respect--and fear. But when an innocent woman dies in an ill-fated shootout, Gage decides it's time to drop his guns and change his wicked ways. There's just one problem: There is no rest for the wicked. A nameless drifter haunted by his past, Gage hopes to right the wrongs he committed. He's fighting on the side of the angels now, whether it's a widow losing her freight business, a wagon train of farmers in trouble, or a small-time rancher battling a big-time cattle baron. Wherever he goes, there are wicked men preying on the innocent--and some of them recognize Gage as the notorious Texas Lightning. Gage knows he can't outrun his demons. But he can still outgun them..."--